Pengaruh Pemanfaatan Aplikasi Keluarga Sehat terhadap Kinerja Petugas Promosi Kesehatan Puskesmas - Ekowati, Ekowati; Shaluhiyah, Zahroh; Agushybana, Farid (Jurnal Promosi Kesehatan Indonesia, 2019)
Background: Keluarga Sehat (KS) application is a system  to provide data and information about family’s health which expected to have benefit to the programmer in developing health promotion planning in health center. The benefit of this program would be maximized when man,organization and technology support each other. This study aims to evaluate the utilization of KS application and its effect to the performance of health promotion programmer in developing health programs.Method: This is quantitative study with cross sectional approach to identify and examine  causal relationships between user satisfaction, system utilization and health staff performance in health promotion programs. There were 60 health promotion staffs from health centers  who were trained about KS application in 2016-2018 by Ministry of Health or Pati and Semarang City Health Offices were involved in this study. Independent variables consists of system quality, information quality, personal capability, leadership or management support, co-worker support and availability of facilities. Whilst, dependent variables consists of user satisfaction, system utilization and performance of health promotion staffs. The analysis of the system refers to HOT-Fit Model. Results: Personal capability, system utilization, leadership or management supports have  significantly positive influence on the performance of health promotion staffs. User satisfaction, co-worker support, availability of facilities, system quality and information quality both directly and indirectly through user satisfaction and system utilization did not have any significant influence on the performance of health promotion staffs. It is recommended to provide training in processing and analyzing data from the application as well as strengthening internet network and adding the server.